True aneurysms of the inferior phrenic arteries in celiac trunk compression syndrome and surgical treatment of three patients - A. M. Ignashov; A. V. Kochetkov; A. N. Morozov; M. A. Stalkov; S. D. Migashchuk; V. I. Kornev; I. A. Samusenko; A. Yu. Gichkin; Yu. A. Ignashov (Вестник хирургии имени И.И. Грекова)
The Objective was to pay attention to the rare combination of a true aneurysm of the inferior phrenic artery and the syndrome of compression of the celiac trunk, its open decompression and elimination of aneurysms in three patients.Methods and Materials. From September 2018 to December 2022, in 5 patients with celiac trunk compression syndrome (three men; mean age 49.4 years, from 18 to 72 years) out of 182, according to MSCT angiography and during surgery, an aneurysm of the right inferior phrenic artery was detected in two and left for three. These arteries originated from the post-stenotic moderately dilated part of the celiac trunk.Results. On average, its diameter at the site of stenosis was 1.9 mm and the degree was 58 %, the trunk was 8.6 mm and the aneurysm was 6.8 mm, and its length was 8 mm. In 4 cases, the aneurysm originated from the ostium of this artery and in one case, 5 mm from it, without involvement of the celiac trunk. All 5 aneurysms were concentric sac-shaped, including a funnel-shaped variant in two of them. Three out of 5 patients successfully underwent open decompression of the celiac trunk and immediately resection of the aneurysm in two with the imposition of a lateral suture and ligatures on the artery, respectively, and exclusion in one with a purse-string suture.Conclusion. An aneurysm of the inferior phrenic artery originating from the celiac trunk may be one of the specific manifestations of its long-term significant diaphragmatic compression. With such a combination of lesions, the expediency of decompressing the celiac trunk and removing the aneurysm from the bloodstream, regardless of its size, should be considered.